Biomechanical Movement Analysis Of Shooting In Basketball In Professional Athletes Golden State Warriors: A Case Study Of Stephen Curry - Ilham Maulana; Fadhillah Irsyad Rahman; Qorry Armen Gemael; Deden Akbar Izzuddin (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study investigates the biomechanics of Stephen Curry's shooting technique, focusing on the factors contributing to his unparalleled accuracy in basketball, particularly for long-range shots. Using a quantitative descriptive approach, biomechanical analysis was performed by examining kinematic and kinetic parameters derived from video recordings of NBA games. Key body mechanics, including the coordination of the lower body for propulsion and the upper body for precision, were analyzed using motion capture systems and software like Kinovea. The findings reveal that optimal joint angles are critical for shot success: a knee angle of approximately 45 degrees during the propulsion phase and an elbow angle of 90 degrees at shot release. The study highlights that a ball trajectory with an elevation angle of 45-50 degrees significantly enhances scoring potential. Moreover, the speed of the ball at release, averaging 30-35 mph for three-pointers, plays a crucial role in shot stability and accuracy. The research emphasizes the importance of biomechanical principles, such as the efficient transfer of kinetic energy from the lower to the upper body, precise wrist rotation, and ideal trajectory, in improving shooting performance. These insights underline the need for basketball coaches and players to adopt training techniques informed by biomechanical data. Enhancing body positioning, lower body strength, and ball control are essential for developing more effective shooting skills. The study concludes that mastering biomechanical principles provides a significant edge in professional basketball performance, offering valuable perspectives for athletes and trainers alike.